MEDIA KOMIK MATEMATIKA DIGITAL UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI DAN RESILIENSI MATEMATIS SISWA - Atika Hidayah; Netriwati; Fraulein Intan Suri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to develop digital mathematics comic media to improve students' mathematical representation and resilience skills. The research method used is Research and Development (R&D) by adopting the DDD-E (Decide, Design, Develop, and Evaluate) model. The results of this development research are in the form of digital mathematics comic media on the material of lines and angles that can be accessed via gadgets online. The level of product validation is obtained from the assessment of the expert team, namely material validation 4.43 with the category "very valid" and media validation 4.76 with the category "very valid". Then the digital math comic media was declared effective in improving students' mathematical resilience abilities with an average N-Gain score of the experimental class of 0.44, better than the N-Gain score of the control class of 0.01. And the increase in students' mathematical representation abilities using digital math comic media with an average N-Gain of 0.49 was not greater than students who used conventional learning media with an average N-Gain of 0.38.